„Droga serca” w doświadczeniu i refleksji św. Augustyna - Mejzner, Mirosław (Collectanea Theologica, 2016)
In the writings of St. Augustine, the Latin word cor occurs more than 8,000 times, being one of the most important, though ambiguous, terms of his anthropology and spirituality. As a synonym for the inner man (homo interior) it encompasses the whole life: affective, intellectual, moral and religious. In this sense, it is the privileged place for a personal encounter with God. Analysis of Augustine’s writings reveals a link between the concept of the Trinity and indications concerning the spiritual life of man. Reflections on the “heart” can be put into a kind of triptych: creation “in the image of God”, enlightenment by Christ, and expansion by the Holy Spirit. The impact of God on the human heart should find their completion in a voluntarily adopted attitude of adoration, humility and love.